2012
DOI: 10.1253/circj.cj-11-1419
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Right Atrial Magnetic Strength Is a Novel Predictor of Recurrence of Atrial Fibrillation After Radiofrequency Catheter Ablation

Abstract: Background: Differences in electrical properties between left and right atria (LA and RA) after pulmonary vein isolation (PVI) for atrial fibrillation (AF) are currently poorly understood. Magnetocardiograms were used to investigate the effect of PVI on bi-atrial magnetic field changes and their relationship to clinical outcomes. Methods and Results:This study included 71 patients undergoing PVI for paroxysmal AF. Magnetocardiograms were recorded at baseline and 1 day, 8 weeks, and 24 weeks after ablation. Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It was proposed that the term QRS d /QRS could be a surrogate marker of CV dispersion coefficient based on the standard deviation of the mean CV [68]. Other non-invasive methods of assessing the function of the heart include magnetocardiography, which may provide additional insights into risk stratification in the future [69], [70], [71], [72], [73], [74], [75], [76].…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that the term QRS d /QRS could be a surrogate marker of CV dispersion coefficient based on the standard deviation of the mean CV [68]. Other non-invasive methods of assessing the function of the heart include magnetocardiography, which may provide additional insights into risk stratification in the future [69], [70], [71], [72], [73], [74], [75], [76].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome for NPAF (36%) was less satisfactory but still better than after ostial PVI as determined by Weerasooriya et al 20 Predictors of Very Late Recurrence After Circumferential Ablation of AF Many factors (type of AF, LA size, age, sleep apnea and obesity, hypertension, LA fibrosis detected on magnetic resonance imaging [MRI], diabetes, rise in right atrium magnetic strength) have been proposed as predictors of poorer outcome after PVI. 19, 30 The most consistent predictor of very late recurrence was type of AF, followed by LA size. 19 We found that the independent predictors of very late recurrence of AF after circumferential RF ablation were: type of AF, size of LA, and impairment of renal function.…”
Section: Long-term Pre-procedural Predictors Of Af Ablationmentioning
confidence: 98%
“…Many factors (type of AF, LA size, age, sleep apnea and obesity, hypertension, LA fibrosis detected by magnetic resonance imaging, diabetes, a rise in right atrium magnetic strength) have been proposed as predictors of a poorer outcome after PVI [18,19] but the discrepancies among authors [20][21][22][23][24][25] showed the complicated nature of already ablated atrial tissue. We applied a combined ALARMEc risk score which effectively discriminates patient outcome after any ablation procedure [4,5].…”
Section: Alarmec Risk Score and Long-term Successmentioning
confidence: 99%